Determination of the combined effect of chemical modification and compression of agatis wood on the dimension stability, termite resistance, and morphological structure - H. P. Shawkataly, Abdul Khalil; Rudi Dungani,; Mohammed, Issam Ahmed; Hossain, Md. Sohrab; N. A., Sri Aprilia; Edy Budiarso,; Enih Rosamah, (College of Natural Resources, North Carolina State University, 2014)
Agatis wood (Agathis lorantifolia Salisb.) was impregnated with a combination of styrene and methyl methacrylate and compressed to a strain of 50% to improve dimensional stability and termite resistance. The changes in cell structure were analyzed to determine the effects of the combination treatment. The results showed that densification of agatis wood with compression, impregnation, and a combination of treatments resulted in an increase in physical properties (density and dimensional stability) by changing the cellular structure and chemical components (i.e., cellulose crystallinity, microfibril angle, and preferred orientation of fibers) as well as degradation of cellulose. The chemical modification and combination treatment (chemical and compression) of wood generally led to a high resistance to dry wood termites.